Structurally Well‐Defined Au@Cu2−xS Core–Shell Nanocrystals for Improved Cancer Treatment Based on Enhanced Photothermal Efficiency. Issue 16 (23rd February 2016) - Ji, Muwei; Xu, Meng; Zhang, Wei; Yang, Zhenzhong; Huang, Liu; Liu, Jiajia; Zhang, Yong; Gu, Lin; Yu, Youxing; Hao, Weichang; An, Pengfei; Zheng, Lirong; et al.
Abstract : Au@Cu2− x S core–shell nanocrystals (NCs) have been synthesized under large lattice mismatch with high crystallinity, controllable shape, and nonstoichiometric composition. Both experimental observations and simulations are used to verify the flexible dual‐mode plasmon coupling. The enhanced photothermal effect is harnessed for diverse HeLa cancer cell ablation applications in the NIR‐I window (750–900 nm) and the NIR‐II window (1000–1400 nm).